EFEK PENGGUNAAN ANALGETIK DALAM KEBERHASILAN PERAWATAN ORTODONTI (LITERATURE REVIEW) - Edrizal Edrizal; Yenita Alamsyah; Oktafiana Hendafis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Orthodontic treatment is a treatment that aims to obtain a good dentofacial relationship aesthetically by improving the arrangement of crowded teeth, correcting tooth-tooth irritation, correcting the relationship between incisals and creating a good occlusion relationship. Orthodontic treatment requires a light and continuous force that corresponds to the vascular pressure in the periodontal ligament. Some of the complications that occur when installing an orthodontic appliance are pain. To relieve pain, the orthodontist will prescribe drugs such as analgesics, but there are some analgesics that can inhibit prostaglandin synthesis and result in slow tooth movement. The aim of this literature review is to investigate the effect of using analgesics on tooth movement during orthodontic treatment. The research method used in this research is literature review. The results showed that the number of analgesics reviewed in the literature review were aspirin, diclofenac, indomethacin, ibuprofen, naproxen, celecoxib, acetaminophen and piroxicam which affected autodontic treatment. Acetaminophen and celecoxib have no effect on bone resorption and tooth movement. The conclusion from this literature review is that the use of analgesics has an effect on the success of orthodontic treatment.Keywords: A analgesics, pain and orthodontic